2011
DOI: 10.1371/journal.pone.0019988
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Inhibitory Effects of Fetal Liver Mesenchymal Stem Cells on T-Lymphocyte Proliferation

Abstract: Human bone marrow mesenchymal stem cells (BM-MSC) are multipotent progenitor cells that have transient immunomodulatory properties on Natural Killer (NK) cells, Dendritic Cells (DC), and T cells. This study compared the use of MSC isolated from bone marrow and fetal liver (FL-MSC) to determine which displayed the most efficient immunosuppressive effects on T cell activation. Although both types of MSC exhibit similar phenotype profile, FL-MSC displays a much more extended in vitro life-span and immunomodulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 44 publications
5
75
0
Order By: Relevance
“…We noted that BM-MSCs, UCB-MSCs, and to a lesser extent PL-MSCs, suppressed the proliferation of anti-CD3/CD28-activated CD3 + T cells only in the presence of direct contact between the two cell populations; similar results were previously obtained with mouse BMMSCs [23]. Moreover, several studies have reported that a lack of cellular contact affects MSCs-mediated immunosuppression because the reduction of activated T-cell proliferation was less apparent [8,[20][21][22]30,46,47].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We noted that BM-MSCs, UCB-MSCs, and to a lesser extent PL-MSCs, suppressed the proliferation of anti-CD3/CD28-activated CD3 + T cells only in the presence of direct contact between the two cell populations; similar results were previously obtained with mouse BMMSCs [23]. Moreover, several studies have reported that a lack of cellular contact affects MSCs-mediated immunosuppression because the reduction of activated T-cell proliferation was less apparent [8,[20][21][22]30,46,47].…”
Section: Discussionsupporting
confidence: 81%
“…In this regard it has been shown that expression of adhesion molecules ICAM-I and VCAM-I on MSCs decline proliferation of splenocytes activated with anti-CD3 antibodies [48] and further, both adhesion molecules have the capacity to induce CTLA-4 expression on T cells [49], which is involved in inhibition of T-cell proliferation [33,34]. In addition, cell contact between MSCs and T cells increase expression of IL-10, HLA-G1, and HLA-G5 immunosuppression molecules [7,8,19,21], which are involved in the inhibition of T-cell proliferation. It appears that HLA-G1, whose expression is increased on MSCs cocultured with activated T cells [21], is the molecule responsible to stimulate initial secretion of IL-10, which stimulate HLA-G5 secretion in MSCs and through a positive feedback mechanism stimulate secretion of IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that despite previously published data suggesting the importance of IL-10 in MSC-mediated immunosuppression [40][41][42], to our knowledge, no one has yet demonstrated that the putative effects of IL-10 could be reversed by blocking the IL-10 pathway. Such a discrepancy may not only be explained by the redundancy of MSC-induced inhibitory mechanisms [43][44][45], but also by the simple fact that while IL-10 + IFNg + T-cells are being generated during the first stimulation by the presence of MSCs, their accumulation occurs too late to have any effect.…”
Section: Cd25mentioning
confidence: 82%
“…33 An association between HLA-G and T-cell tolerance was suggested by Naji et al 33 who found a correlation between soluble HLA-G plasma levels, percentages of CD3 + CD4 low and CD3 + CD8 low suppressor T cells, and graft acceptance in liver/kidney transplanted patients. In addition, in a very recent study, Giuliani et al 34 reported an in vitro expansion of CD3 + CD4 low and CD3 + CD8 low T cells by mesenchymal stem cells in an HLA-G mediated fashion.…”
Section: Discussionmentioning
confidence: 99%